Measuring User Engagement with a Socially Connected, Gamified Health Promotion Mobile App - White, Becky; Burns, Sharyn; Giglia, Roslyn; Dhaliwal, Sayvinder; Scott, Jane (2022)
Participant engagement is an important consideration in mHealth interventions and there are no standardised measurements available to guide researchers. This paper describes the engagement index customised for the Milk Man app, a mobile app designed to engage fathers with breastfeeding and parenting information. Participants were recruited from maternity hospitals in Perth, Western Australia. An engagement index with scores ranging from 0 to 100 was calculated. Kaplan Meier survival analysis was used to determine difference in duration of exclusive breastfeeding, and Pearson’s chi square analysis was conducted to investigate the association of engagement level with demographic characteristics and exclusive breastfeeding at 6 weeks. While overall, partners of participants who installed Milk Man were less likely to have ceased exclusive breastfeeding at any time point from birth to six weeks postpartum, this result was modest and of borderline significance (log rank test p = 0.052; Breslow p = 0.046; Tarone-Ware p = 0.049). The mean engagement score was 29.7% (range 1–80%), median 27.6%. Engagement level had no impact on duration of exclusive breastfeeding and demographic factors were not associated with engagement level. This research demonstrates a range of metrics that can be used to quantify participant engagement. However, more research is needed to identify ways of measuring effective engagement.